Santificare la vita nei limiti del diritto: Questioni di bioetica ebraica in dialogo con Levinas - Coen, Cosimo Nicolini (Dignità umana, 2024)
The paper takes in exam some issues of Jewish bioethics in light of the relationship between the sacredness of life and its sanctification through the precepts. In dialogue with Levinas’ thought, we shall recognize here a tension between the limits (and a certain moderation) conveyed by the law and the ethical life, which in certain conditions requires, as stated by the Halakhà, the willingness to sacrifice. The Jewish jurisprudence on abortion, organ donation, end of life and assisted reproduction, can be read as an effort to find a balance between these two polarities. Pointing, at last, to the ethical experience of the bios, where the sacredness of life is bound to respect for one’s own dignity and that of the other.